Pengukuran Viskositas Oli metode Induksi Elektromagnetik Berbantuan software Audacity Untuk Praktikum Fluida Zat Cair - Muhammad Subhan; Lis Suswati; Fatimah Fatimah (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The implementation of physics practicum in several schools on certain material is sometimes not carried out optimally by the unavailability of media or measuring instruments with high price factors. This study aims to measure the value of the viscosity of a liquid for physics practicum on liquid fluid materials. The method used is by utilizing two electromagnetic induction coils as distance data and courage as a determinant of time data. The research was carried out by dropping a magnetic ball with a mass of 6,98 x 10-3+ 0,16 Kg and a diameter of 8,8 x 10-3 + 0,24 m on two different brands of oil as a comparison in a PVC tube with a diameter of 0,046 + 0,08 m which has been given two coils with a distance of 0,2 m. The time required for the magnetic ball on ultratec oil is 0,28 + 0,011 second and the value of the viscosity coefficient ( = 1,097 + 0,52 Ns/m2. While in MPX oil the speed of the magnetic ball is 0,24 + 0,01 second and the value of the viscosity coefficient (=0,94 + 0,66 Ns/m2.